2017
DOI: 10.1002/ece3.3588
|View full text |Cite
|
Sign up to set email alerts
|

Effects of temperature and drought on early life stages in three species of butterflies: Mortality of early life stages as a key determinant of vulnerability to climate change?

Abstract: Anthropogenic climate change poses substantial challenges to biodiversity conservation. Well‐documented responses include phenological and range shifts, and declines in cold but increases in warm‐adapted species. Thus, some species will suffer while others will benefit from ongoing change, although the biological features determining the prospects of a given species under climate change are largely unknown. By comparing three related butterfly species of different vulnerability to climate change, we show that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 63 publications
(134 reference statements)
1
17
0
Order By: Relevance
“…Mortality of early life stages (i.e. eggs or early larval instars) due to desiccation stress during drought events has been shown as a key determinant of butterfly vulnerability to climate change 26 . The strongest population decreases in butterflies from dry lowland areas might therefore be related – at least partly – to direct physiological limitations when facing water shortage.…”
Section: Discussionmentioning
confidence: 99%
“…Mortality of early life stages (i.e. eggs or early larval instars) due to desiccation stress during drought events has been shown as a key determinant of butterfly vulnerability to climate change 26 . The strongest population decreases in butterflies from dry lowland areas might therefore be related – at least partly – to direct physiological limitations when facing water shortage.…”
Section: Discussionmentioning
confidence: 99%
“…Although we know that the ability to tolerate dry periods will be key for species' climate change responses, there is a missing link between studies examining water balance mechanisms and the effects of altered precipitation on fitness (Chown et al, 2011). A recent study by Klockmann & Fischer (2017) showed desiccation stress significantly reduced hatching success in butterflies, more so than temperature stress.…”
Section: Precipitation Predictors: Desiccation Resistancementioning
confidence: 99%
“…In egg state, egg quality is affected by temperature [9,10], humidity [10,11], predator [12] and neutral conditions [4], which occur when all parameters are in good condition. The probabilities for positive condition are 0.20, 0.25, 0.25, 0.30 (neutral, temperature, humidity, predator).…”
Section: Butterfly Life Cycle Algorithm (Blca)mentioning
confidence: 99%